Takyiful Urfi pada Perbankan Syariah Indonesia: Studi Fatwa Dewan Syariah Nasional - Budiman (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2022)
This study aims to reconstruct the 138 Fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) according to Urf by using the takyif of Al Adah Muhakkamah fiqh rules. The data comes from 138 fatwas of the 2000-2020 National Sharia Council which are supported by the latest research and articles. The data is then analyzed using takyif fiqh rules with the content analysis method. The data is then verified by an expert in the field of Islamic finance. The results of the reconstruction of the 138 fatwas show that 12 fatwas have mutabaqah with Al'adah Muhakkamah. Al Adah Muhakkamah is classified according to the fatwa which contains the amount of margin for a contract based on buying and selling, the amount of fees on a contract based on rent and wages, and the amount of profit sharing on a contract based on cooperation